Trust based flooding attack detection and response mechanisms for ad hoc on-demand distance vector routing protocol - Ashouruan, Bahram Yaghoubzadeh (2013)
Mobile Ad hoc Networks provide a structure-less environment, enabling participants in the coverage mobile nodes to communicate each other without using any centralized authentication agent. Thus, it is compromised in face to various sorts of attacks. Unfortunately, none of the presented secured routing protocols can detect internal Denial of Service (DoS) attacks by itself naturally. One of the most important and effective internal misbehaviors which has dramatic side effects on the network’s throughput is Flooding Attack. This project aims at proposing an alternative solution to detect and respond Flooding Attack in MANET which is based on cooperative trust evaluation mechanisms. Actually, this approach is matched to basic principles of distributed networks in which the participating nodes are responsible for any needed creation, operation and maintenance of the network. Moreover, it seems useful for high mobility networks where the suspicious nodes move around the area repeatedly. Consequently, the gained results of the project prove that the proposed Trust-based Cooperation mechanisms decreases the side effects of Flooding Attack on Ad-hoc On-demand Distance Vector routing protocol.